Cooperation and cheating as innovation: insights from cellular societies. (5th December 2017) - Aktipis, Athena; Maley, Carlo C.
Abstract : The capacity to innovate is often considered a defining feature of human societies, but it is not a capacity that is unique to human societies: innovation occurs in cellular societies as well. Cellular societies such as multicellular bodies and microbial communities, including the human microbiome, are capable of innovation in response to novel opportunities and threats. Multicellularity represents a suite of innovations for cellular cooperation, but multicellularity also opened up novel opportunities for cells to cheat, exploiting the infrastructure and resources of the body. Multicellular bodies evolve less quickly than the cells within them, leaving them vulnerable to cellular innovations that can lead to cancer and infections. In order to counter these threats, multicellular bodies deploy additional innovations including the adaptive immune system and the development of partnerships with preferred microbial partners. What can we learn from examining these innovations in cooperation and cheating in cellular societies? First, innovation in social systems involves a constant tension between novel mechanisms that enable greater size and complexity of cooperative entities and novel ways of cheating. Second, cultivating cooperation with partners who can rapidly and effectively innovate (such as microbes) is important for large entities including multicellular bodies. And third, multicellularity enabled cells to manage risk socially, allowing organisms to survive in challenging environments where life would otherwise be impossible. Throughout, we ask how insights from cellular societies might be translated into new innovations in human health and medicine, promoting and protecting the cellular cooperation that makes us viable multicellular organisms. This article is part of the themed issue 'Process and pattern in innovations from cells to societies'.